Teachers’ Application of Cohesion Theory to Develop Students’ Written Discourse Competence - Burayou, Zelalem; Disasa, Rufael (JOLLT Journal of Languages and Language Teaching, 2026)
This study investigated teachers’ instructional practices of applying the theory of cohesion in teaching writing skills to develop grade 11 Ethiopian students’ written discourse competence. The participants were selected using purposive sampling. The study employed a descriptive research design. Classroom observation was used to collect the data. The data was analyzed thematically based on the qualitative data analysis framework developed by Braun and Clarke (2021). The theme of the data was developed based on the elements of cohesion: conjunction, references, ellipsis, substitution, and lexical cohesion. The study revealed that the majority of teachers limited the students’ exposure to conjunctions. Additionally, it was found that nearly all of the teachers rarely use strategies that could help students comprehend and employ cohesive devices in their writing. Instead, they avoided the communicative activities and concentrated on distinct sentence-level tasks. Hence, it is essential that the teachers expose the students to cohesive devices fully. The teachers should also employ different techniques that facilitate the students’ ability to employ cohesion in their writing. Textbook writers should also expose the students to different types of cohesive devices. They should also employ various activities that enhance the students’ ability to use cohesive devices in their writing.